Inequalities in dental caries experience among 4‐year‐old New Zealand children. Issue 3 (8th February 2018) - Shackleton, Nichola; Broadbent, Jonathan M.; Thornley, Simon; Milne, Barry J.; Crengle, Sue; Exeter, Daniel J.
Abstract: Objectives: To investigate ethnic‐specific deprivation gradients in early childhood dental caries experience considering different domains of deprivation. Methods: We used cross‐sectional near whole population‐level data on 318 321 four‐year‐olds attending the "B4 School check, " a national health and development check in New Zealand, across 6 fiscal years (2010/2011 to 2015/2016). The " lift the lip " screening tool was used to estimate experience of any caries and severe caries. We investigated deprivation gradients using the Index of Multiple Deprivation (IMD), which measures seven domains of deprivation across 5958 geographical areas ("data zones"). Ethnicity was categorized into five groups: (i) Māori, (ii) Pacific, (iii) Asian, (iv) Middle Eastern, Latin American and African (MELAA) and (v) European & Other (combined). We used a random intercepts model to estimate mutually adjusted associations between deprivation, ethnicity, age, fiscal year, and evidence of any dental caries experience. Results: Reports of any caries experience decreased from 15.8% (95% CI: 15.7; 15.9%) to 14.7% 95% CI: 14.4; 14.8%), while reports of severe caries experience increased from 3.0% (95% CI: 3.0; 3.1%) to 4.4% (95% CI: 4.3; 4.5%) from 2010/2011 to 2015/2016. This varied by ethnicity with larger increases in severe caries for Pacific children from 7.1% (95% CI: 6.8; 7.4%) to 14.1% (95% CI: 13.7; 14.5%). There were deprivation gradients in dental caries experience with considerable variation by ethnicity and by domain of deprivation. The association between deprivation and dental caries experience was weakest for Asian children and was most pronounced for Pacific and Māori children. Conclusion: Socioeconomic gradients in dental caries experience are evident by age 4 years, and these gradients vary by ethnicity and domain of deprivation.